2008
DOI: 10.1038/nature07050
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback sharpens the anaphase switch

Abstract: At the onset of anaphase, sister-chromatid cohesion is dissolved abruptly and irreversibly, ensuring that all chromosome pairs disjoin almost simultaneously. The regulatory mechanisms that generate this switch-like behavior are unclear. Anaphase is initiated when a ubiquitin ligase, the Anaphase-Promoting Complex (APC), triggers the destruction of securin, thereby allowing the protease, separase, to disrupt sister-chromatid cohesion 1-4. Here we demonstrate that Cdk1-dependent phosphorylation of securin near i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
183
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 30 publications
13
183
0
Order By: Relevance
“…There are reports in buddying yeast that Cdk1 phosphorylates securin and protects it from being degraded by APC/C. [32][33][34] However, in human cells Cdk1 is less important in the metaphase-anaphase transition, and the main mechanism is that securin and cyclin B1 inhibit separase activity to protect cohesion so that chromosomes are not able to separate. 34,35 Considering others' findings and our results we conclude that securin is the main molecule that protects cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports in buddying yeast that Cdk1 phosphorylates securin and protects it from being degraded by APC/C. [32][33][34] However, in human cells Cdk1 is less important in the metaphase-anaphase transition, and the main mechanism is that securin and cyclin B1 inhibit separase activity to protect cohesion so that chromosomes are not able to separate. 34,35 Considering others' findings and our results we conclude that securin is the main molecule that protects cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc14 dephosphorylates Securin to target it for ubiquitylation and degradation. Degradation of Securin activates Separase, which also activates Cdc14 (13). Our laboratory and other groups found that Clp1, the Schizosaccharomyces pombe Cdc14 ortholog, dephosphorylates Cdc25 on Cdk1 phosphosites, and this dephosphorylation correlates with Cdc25 inactivation and degradation (17,18).…”
mentioning
confidence: 93%
“…Mitotic exit and the spindle assembly checkpoint may also be modulated by a bistable switch (12)(13)(14). In Saccharomyces cerevisiae, Cdc14, a phosphatase that dephosphorylates Cdk1 substrates (15,16), adds abruptness to the metaphase-anaphase switch by interacting with Securin, a protein that protects sister chromatid separation until anaphase onset in an ultrasensitive positive feedback loop.…”
mentioning
confidence: 99%
“…The phosphorylation of securin by Cdk1 is critical for its binding with separase and also reduces the ubiquitination of itself by APC (Holt et al 2008). In Homo sapiens, pituitary tumortransforming 1 (PTTG1) is a homolog of yeast securin protein for which the function is unknown.…”
Section: Function Of Cdc23 In Thyroid Cancer Cellsmentioning
confidence: 99%